A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean - Mendoza, Jose Christopher E.; Devi, Suvarna S. (Zootaxa, 2017)
A new species of swimming crab, Laleonectes kuriya, is described from the western Indian Ocean (Réunion and southwestern India). The new species is morphologically most similar to the Pacific species, L. nipponensis (Sakai, 1938), but differs primarily in the relative length of the ambulatory legs, as well as in the shape of the malesixth pleomere and the form of the first and second male pleopods.